1979
DOI: 10.1038/bjc.1979.224
|View full text |Cite
|
Sign up to set email alerts
|

Immunity as the predominant factor determining metastasis by murine lymphomas

Abstract: Summary.-The metastatic behaviour of the L5178E (non-M) lymphoma and a highly metastatic subline L51787ES (M) were studied in syngeneic DBA2 mice. The non-M tumour rarely metastasizes in intact syngeneic mice, but produces extensive and rapidly lethal metastases when implanted into irradiated recipients. The metastatic behaviour of the M subline is unaffected by irradiation of the host. By conventional transplantation criteria, the non-M tumour is more immunogenic than the M subline. Both tumours, however, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Since the metastasizing fibrosarcoma line was also found to be less antigenic than the nonmetastasizing line, Alexander (1976a) suggested that the macrophages attracted into the latter were part of an immune response against the tumour cells which inhibited metastasis. Later observations that reduction of macrophage content (Wood & Gillespie, 1975) or suppression of the immune response (Davey et al, 1979) appeared to promote dissemination supported this hypothesis, at least for these tumours. In naturally occurring mammary tumours, however, we found macrophage content to be consistently low, ranging from 2 to 9o%, and thus there is no inverse correlation with spontaneous metastasis, which is infrequent (< 2%, Tarin & Price, 1979).…”
Section: Duration Of Macrophage Adherencementioning
confidence: 89%
“…Since the metastasizing fibrosarcoma line was also found to be less antigenic than the nonmetastasizing line, Alexander (1976a) suggested that the macrophages attracted into the latter were part of an immune response against the tumour cells which inhibited metastasis. Later observations that reduction of macrophage content (Wood & Gillespie, 1975) or suppression of the immune response (Davey et al, 1979) appeared to promote dissemination supported this hypothesis, at least for these tumours. In naturally occurring mammary tumours, however, we found macrophage content to be consistently low, ranging from 2 to 9o%, and thus there is no inverse correlation with spontaneous metastasis, which is infrequent (< 2%, Tarin & Price, 1979).…”
Section: Duration Of Macrophage Adherencementioning
confidence: 89%
“…Changes which took place at the cell surface of these cells included carbohydrate side chains (23,24), lymphoid cell surface differentiation antigens (25), Fcr receptors (26), and receptors for Semliki-Forest Virus (27). Compared to Eb, ESbtype cells expressed more microvilli (18), showed increased shedding of surface antigens and vesicles (26,28), and had generally a higher morphological flexibility (deformability) (29) and a higher motility (30). ESb but not Eb cells had the ability to bind in vitro to normal adult cells from involved organs, namely liver (31) and lung (32).…”
Section: Eb/esb Tumor Model System: Etiology and General Characteristicsmentioning
confidence: 99%
“…The results revealed two conditions under which even the parental line Eb could give rise to internal metastases. One was upon inoculation via the intravenous route and the other upon s.c. inoculation into a host preirradiated with 500 rads (30,47). At a s.c. site in a normal host, Eb tumor cells grew progressively without establishing metastases.…”
Section: Spontaneous Variants From the Tumor And The Host" Detectionmentioning
confidence: 99%
“…The metastatic potential of induced and "dormant" metastases was of interest, since it has been suggested that metastases develop from subpopulations of cells of unique metastasizing ability, preexisting within primary tumours (Poste & Fidler,1 980 (Davey et al, 1979). Thus it is suggested thlat, for anaplastic tuimoturs in which the population is inherently highly clonogenic (i.e.…”
Section: Growth Rates Of Tumoursmentioning
confidence: 99%